Cuticle sclerotization determines the difference between the elastic moduli of locust tibiae. (February 2020) - Li, Chuchu; Gorb, Stanislav N.; Rajabi, Hamed
Abstract: A striking characteristic of insect cuticle is the wide range of its material property values, with respect to stiffness, strength and toughness. The elastic modulus of cuticle, for instance, ranges over seven orders of magnitude in different structures and different species. Previous studies suggested that this characteristic is influenced by the microstructure and sclerotization of cuticle. However, the relative role of the two factors in determining the material properties of cuticle is unknown. Here we used a combination of scanning electron microscopy (SEM), confocal laser scanning microscopy (CLSM) and nanoindentation, to investigate the effect of microstructure and sclerotization on the elastic modulus of tibiae of desert locusts. Our results showed that tibial cuticle is an anisotropic material with the highest elastic modulus along the tibial axis. This is likely because majority of the fibers in the cuticle are oriented along this axis. We also found that the hind tibia has a significantly higher elastic modulus, compared with the fore and mid tibiae. This is likely due to the higher sclerotization level of the hind tibia cuticle, and seems to be an adaptation to the locust locomotion by jumping, in which axial loads in the hind tibiae may reach several times the insect body weight. Our results suggest that while sclerotization determines the difference between the elastic moduli of the tibiae, anisotropic properties of each tibia is controlled by the specific fiber orientation. Our study provides one of only a few comprehensive investigations on insect cuticle, and helps to better understand the structure-material-function relationship in this complex biological composite. Statement of significance: Insect cuticle is a biological composite with strong anisotropy and wide ranges of material properties. Using an example of the tibial cuticle of desert locusts, we examined the role of two influential factors on the elastic modulus of cuticle: microstructure and sclerotization. Our results suggested the strong influence of sclerotization on the variation of the elastic modulus among fore, mid and hind tibiae, and that of the microstructure on the anisotropy of each tibia. Our results deepens the current understanding of the structure-material-function relationship in complex insect cuticle. Graphical abstract: Image, graphical abstract